Acute myocardial infarction following psoralen plus ultraviolet light therapy - SARI, İBRAHİM; SÜNBÜL, MURAT (W B SAUNDERS CO-ELSEVIER INC, 2013)
Psoralen plus ultraviolet light therapy (PUVA) combines the administration of psoralen with an exposure to ultraviolet A radiation. Psoralen plus ultraviolet light therapy is used for the treatment of a variety of skin diseases including morphea and generally considered as a safe treatment modality. We present here a rare case of 65-year-old woman presented with acute myocardial infarction following PUVA session, which has not been reported previously.
Keywords: LOCALIZED SCLERODERMA; PHOTOCHEMOTHERAPY; MORPHEA; PUVA